A Spanish Version of the Achievement Task Value Scale for University Students: Internal, Convergent, and Criterion Validity and Reliability in Argentinian Students - Sánchez Rosas, Javier; Lou, Yu-Chiung; Lin, Hsiao-Fang; Larroza, Silvana (Pensando Psicología, 2017)
Objective: An Achievement Task Value Scale Spanish Language Adjusted Version, assessing task value items corresponding to importance, utility, interest and cost, was evaluated regarding its psychometric properties, in a sample of Argentine students.Method: In order to assess internal structure, exploratory and confirmatory strategies have been used. Besides, scale convergence was assessed by relating them with a one-dimensional task value scale. Evidences of criterion validity were supported by relating scales with enjoyment, achievement goals, and attention. Finally, internal consistency was estimated using Cronbach’s Alpha and Omega coefficients.Conclusions: Results allow to state that this version of the instrument makes it possible to assess, in a reliable and valid way, three components of task value: utility, interest, and cost.
Keywords: achievement goals; attention; enjoyment; expectancy-value theory; scale; task value